2008
DOI: 10.1038/sc.2008.132
|View full text |Cite
|
Sign up to set email alerts
|

Home aids and personal assistance 10–45 years after spinal cord injury

Abstract: Objective: Assessment of home aids, adaptations and personal assistance received after traumatic spinal cord injury (SCI). Setting: Clinic for Spinal Cord Injuries, Denmark. Uptake area, 2.5 million inhabitants. Study design and methods: Cross-sectional follow-up with retrospective data from medical files. Materials: Individuals with traumatic SCI before 1 January 1991, still in regular follow-up and with sufficient medical record. In all, 279 were included, and 236 answered the questionnaire (193 men and 43 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…The information is important because it provides a benchmark for comparisons with other countries 8 and helps pave the way for discussions about policies on appropriate equipment prescription. The results also provide an indication of the typical cost of equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information is important because it provides a benchmark for comparisons with other countries 8 and helps pave the way for discussions about policies on appropriate equipment prescription. The results also provide an indication of the typical cost of equipment.…”
Section: Discussionmentioning
confidence: 99%
“…4 This policy gives therapists prescribing equipment considerable autonomy perhaps similar to that noted in countries such as Sweden 11 and Denmark who also report high rates of satisfaction and equipment usage. 8 It also enables and encourages patients to trial different types of equipment empowering them and possibly contributing to satisfaction. 2 Needless to say trialling different types of equipment is a time consuming process and cannot be easily done on an outpatient basis.…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers also perform a range of duties and roles including support for ADLs, nursing care, prevention of secondary health conditions, housekeeping, emotional care and practical care (errands). 9,16,17,22 The range of duties and roles identified in these studies may help explain the range in amount of informal care. Although some studies may have had clear operational definitions of what constituted care, these varied widely across studies.…”
Section: Description Of Caregiversmentioning
confidence: 99%
“…Table 2 lists descriptive studies that were included. Of these studies, one reported the results of research with caregivers themselves, 9 nine reported research with individuals with SCI 8,[16][17][18][19][20][21][22][23] and one reported results of research with both caregivers and individuals with SCI. 24 The study that reported research with caregivers only was specific to informal caregiving.…”
Section: Level Of Evidencementioning
confidence: 99%
“…This stage involves establishing the overall research objectives, including the primary purpose of the questionnaire, its target population and proposed format, and the theoretical underpinnings of the research (Crocker & Algina, 1986;Portney & Watkins, 2009 Biering-Sørensen et al, 2009;Friesen, Theodoros, et al, 2015c). Rehabilitation services for…”
Section: Stage 1: Establish the Research Objectives For The Questionnmentioning
confidence: 99%